Long-term follow-up after discharge witnesses a slow decline of insulin autoantibodies in patients with insulin autoimmune syndrome complicated with Grave’s disease: a report of two cases - Lili Zhao; Jinzhi He; Shandong Ye; Chao Chen; Jie Zhu; Chunchun Xiao; Tingni Wu; Zhicheng Liu (BMC Endocrine Disorders, 2023)
Abstract Background Insulin autoimmune syndrome (IAS) is a rare cause of hypoglycemia characterized by high levels of blood insulin autoantibodies. It has been documented that drugs containing sulfhydryl groups may result in IAS. In this study, we present two cases of IAS induced by methimazole, along with their corresponding treatments and a long-term follow-up after hospitalization. Case presentation We report two patients with Grave’s disease (GD), carrying the HLA-DRB1 04:06 genotype, who experienced hypoglycemic episodes after taking methimazole. Inpatient treatments helped return their blood glucose levels to normal. Although no recurrences of hypoglycemia were present in the two cases studied, insulin autoantibodies remained positive for the previous follow-up sessions, which turned negative only three years after discharge. Conclusions GD patients who carry the HLA-DRB1 04:06 genotype are prone to IAS if they take drugs containing sulfhydryl groups. It may take time for the elimination of insulin autoantibodies after the recovery from the hypoglycemic episode in IAS patients.